Characterization of solitary internal waves in the northern Bali waters - Jayanti Nuning; Wicaksono Ashari; Purwandana Adi (BIO Web of Conferences, 2024)
Internal solitary wave (ISW) is an underwater wave, formed due to the evolution of internal tides. The presence of breaking ISWs in coastal areas can potentially influence coastal ecosystems through cross-shelf exchange mechanisms. The southern waters of the Kangean Island and the eastern waters of the Madura Island, known also as part of the northern Bali waters, have been an active habitat for ISW propagation. This study aims to identify and characterize ISW which potentially breaking onshore the Southern Kangean Waters (SKW) and the Eastern Madura Waters (EMW) using Sentinel 1 SAR (Synthetic Aperture Radar) imagery. ISW characterization was carried out using the Korteweg-de Vries (KdV) model. The ISW amplitudes which propagate to EMW varies from 1 - 28 m with a propagation speed of 1.60 - 1.98 m/s, while the ISW which propagate to the SKW has an amplitude of 1 - 60 m with a propagation speed of 0.83 to 2.17 m/s. The results show that the ISW propagating to the SKW has stronger amplitude, phase velocity, and horizontal-vertical velocities than the ISW propagating to the EMW. The maximum speed of the horizontal current triggered by ISW leading to the EMW is 0.03 - 0.17 m/s and the vertical velocity 0.11 - 4.53 cm/s; the maximum speed of horizontal velocity leading to the SKW is 0.02 - 1.29 m/s and the maximum speed of the vertical velocity 0.04 - 19.03 cm/s.